Dog registration hanging on a tooth: a case report - Crespi, Julián Alejandro (2024)
Dog breeder associations have regulations for the registration and breeding of their individuals. The complete dentition is between them, thus the absence of first and second molars prevents the registration of specimens. A dispute arose when the registration of a 20-month-old male dog was rejected by the Argentine club of German Shepherd Dog Breeders, because the second lower right molar was absent in routine examination. The breeder appealed the decision, alleging that the absence of the molar was accidental and not for a genetic reason, providing as evidence a molar found in his breeding kennel. Our laboratory was consulted with the objective of determining the genetic relationship between the oral swab sample obtained from the rejected dog (reference), and the molar found (evidence). For this reason, genotyping was carried out through the use of microsatellites. The results confirmed that the samples shared the same DNA profile, with the molar found being between 1.00E+11 and 1.27E+17 times more likely to have come from the dog to be registered than from an animal taken at random from the reference population. To date, there are no known reports of a similar dispute, resolved by studying a DNA profile using a tooth.